REHABILITATION OF PATIENTS AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION USING INTERNAL BRACE TECHNIQUE - Klaudia Bilińska; Anna Szot; Joanna Węgrzecka; Kazimierz Czajka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Anterior cruciate ligament (ACL) injuries are among the most common and functionally limiting conditions in physically active individuals. Although traditional ACL reconstruction techniques are effective in restoring knee stability, they are associated with prolonged rehabilitation, potential graft failure, and psychological barriers to returning to sport. The Internal Brace Ligament Augmentation (IBLA) technique has emerged as a biomechanically enhanced alternative that may overcome some of these limitations. Materials and Methods: This narrative review is based on a literature search conducted in PubMed, Web of Science, and Google Scholar using the keywords: ACL reconstruction, Internal Brace, rehabilitation, and return to sport. Studies were included if they addressed ACL reconstruction using the IBLA technique, with a focus on rehabilitation protocols, functional outcomes, and comparisons with standard ACL reconstruction methods. Results: Current evidence suggests that the Internal Brace technique provides improved graft stability and reduces elongation during early loading phases. These advantages may support faster mobilization and progression through rehabilitation. Clinical data indicate the potential for earlier return to sport with functional outcomes comparable or superior to traditional techniques. Nonetheless, standardized rehabilitation protocols specific to IBLA remain underdeveloped, and long-term outcome data are still limited. Conclusions: Internal Brace Ligament Augmentation represents a promising innovation in ACL reconstruction, offering mechanical support that may enable accelerated and safer rehabilitation. While preliminary findings are encouraging, further high-quality research is needed to confirm long-term efficacy and establish evidence-based rehabilitation guidelines. The integration of biomechanical and clinical insights may improve functional recovery and return-to-sport success in active populations.